Grace : more than we deserve, greater than we imagine - Lucado, Max. (Nashville, Tenn. : Thomas Nelson, 2012)
In this book the author, America's pastor defines God's grace and illuminates the changes it can bring into a person's life. Grace. We talk as though we understand the term. The bank gives us a grace period. The seedy politician falls from grace. Musicians speak of a grace note. We describe an actress as gracious, a dancer as graceful. We use the word for hospitals, baby girls, kings, and premeal prayers. We talk as though we know what Grace means. But do we really understand it? Have we settled for wimpy Grace? It politely occupies a phrase in a hymn, fits nicely on a church sign. Never causes trouble or demands a response. When asked, "Do you believe in Grace?" who could say no? In this book, the author asks a deeper question: Have you been changed by Grace? Shaped by Grace? Strengthened by Grace? Emboldened by Grace? Softened by Grace? Snatched by the nape of your neck and shaken to your senses by Grace? God's Grace has a drenching about it. A wildness about it. A white water, riptide, turn you upside downness about it. Grace comes after you. It rewires you. From insecure to God secure. From regret riddled to better because of it. From afraid to die to ready to fly. The author here makes an effort to help us understand that Grace is the voice that calls us to change and then gives us the power to pull it off, that Grace is another word for God's reservoir of strength and protection, and that God has enough grace to pardon every sin, solve every dilemma, wipe every tear, and answer every question.
Grace-shaped life -- God who stoops -- O sweet exchange -- You can rest now -- Wet feet -- Grace on the fringe -- Coming clean with God -- Fear dethroned -- Unscrooged hearts -- Chosen children -- Heaven guaranteed -- Conclusion, when grace happens -- Reader's guide.
"1358279"
Includes bibliographical references.
Keywords: Grace (Theology)